Relationship-Based Resource Allocations: Evidence from the Use of "Guanxi" during SEOs. (15th August 2018) - Brockman, Paul; Firth, Michael; He, Xianjie; Mao, Xinyang; Rui, Oliver
Abstract : We examine the role of relationship-based resource allocations during the approval process of seasoned equity offerings (SEOs) in the Chinese capital market. Our results show that guanxi-based relationships significantly increase the likelihood of SEO approvals, particularly for suspect SEO applicants with abnormal levels of earnings management (EM), related-party transactions (RPTs), and intercompany loans. More importantly, we find that guanxi-influenced SEO firms have significantly poorer performance in the post-SEO period, which indicates that it results in inefficient resource allocations. Overall, our evidence suggests that relationship-based resource allocations lead to negative spillover effects that impose social welfare losses.